Perinatal phthalates exposure decreases fine-motor functions in 11-year-old girls: Results from weighted Quantile sum regression. (March 2020) - Daniel, Sharon; Balalian, Arin A.; Whyatt, Robin M.; Liu, Xinhua; Rauh, Virginia; Herbstman, Julie; Factor-Litvak, Pam
Highlights: Mixture of all phthalates was associated with lower fine motor scores among girls. Mixture of non-DEHP phthalates was associated with girls' lower fine motor scores. Mixtures of phthalate metabolites and gross motor scores were not associated. Abstract: Introduction: Phthalates are a group of high production chemicals, generally used as plasticizers and odor enhancers. Phthalates cross the blood-placenta barrier and are associated with deficits in cognitive functions and behavior problems in offspring. We previously reported sex-specific associations with motor function when phthalates are considered singly. Because exposure to phthalates usually occurs as mixtures, here we assess these associations between a mixture of phthalates and motor function at age 11 years. Methods: Data come from the prospective cohort study of mothers and offspring who participated in the Columbia Center for Children's Environmental Health birth cohort (CCCEH). Seven phthalate metabolites were measured in maternal spot urine obtained during the third trimester and motor function was evaluated using the short form of the Bruininks-Oseretsky Test of Motor Proficiency, 2nd edition (BOT-2) at the age of 11 years. We used Weighted Quartile Sum (WQS) regression models to examine the effect of phthalate metabolites in males and females separately. The models were adjusted for child age in months, child BMI, maternal race (African-American vs. Dominican), prenatal alcohol consumption, maternal demoralization score, HOME score, and urine specific gravity. In a secondary analysis we used linear regression models to examine the association between the sum of molar concentrations of both DEHP and non-DEHP metabolites, and outcomes of gross and fine motor functions. Results: 209 mother-child pairs were eligible for this analysis. A significant decrease in fine-motor functions was observed among females, but not among males, following exposure to high levels of weighted quartile sum of seven phthalate metabolites (Covariates-adjusted coefficient estimate B = −2.7, 95% Confidence Interval [CI] −4.64 to −0.75, p = 0.01 for females [n = 116] and B = −1.63, 95%CI −3.94 to 0.69, p = 0.16 for males [n = 93]). The most highly weighted phthalate metabolites, associated with fine-motor functions among females, were MBP, MBZP, and MIBP, all non-DEHP phthalates. No significant associations were found between the weighted quartile sum of seven phthalate metabolites and gross-motor functions at the age of 11 years for males (B = −0.81, 95%CI −1.17 to 1.96, p = 0.23). With the molar sum of four non-DEHP phthalates as main predictor of linear regression models, we found significant decrease in gross and fine motor functions among females prenatally exposed to non-DEHP phthalates B = −0.98, 95%CI −1.98 to 0.03, p = 0.05 and B = −0.85, 95%CI −1.49 to −0.20, p = 0.01, respectively). Conclusions: Phthalate exposure during pregnancy was associated with decreased motor functions among 11-year-old girls.